Strategi Pemasaran Klinik Pratama Mutiara Bunda Tabanan berbasis SWOT untuk Meningkatkan Kunjungan Pasien - Himawan, I Made Fajar Sutrisna; Purwadhi, Purwadhi; Suwardhani, Achmad Dheni (Metta : Jurnal Ilmu Multidisiplin, 2024)
This study aims to evaluate the marketing strategy of Klinik Pratama Mutiara Bunda Tabanan to increase patient visits and strengthen the clinic's position in the local market. The clinic faces challenges in capitalizing on external opportunities despite having strong internal strengths and suboptimal marketing strategies. The research employs SWOT analysis, IFE and EFE matrix mapping, and interviews with clinic management and staff. Based on the SWOT analysis, the clinic is positioned in Quadrant II, indicating potential for growth if internal strengths are fully leveraged and challenges are addressed. The study recommends strategies to increase patient visits, including combining social media promotions with direct outreach, improving service quality by hiring specialist doctors, and forming partnerships with BPJS (the Indonesian National Health Insurance Program). These measures are expected to expand the market, enhance patient satisfaction, and strengthen the clinic's position in the local healthcare sector. The study concludes that Klinik Pratama Mutiara Bunda has the potential to overcome external challenges by improving service quality and implementing more effective marketing strategies, enabling the clinic to increase its competitiveness and long-term performance.